Seed Dormancy Dynamics and Germination Characteristics of Malva parviflora L. - Rakesh Dawar; Vishwanath Rohidas Yalamalle; Ram Swaroop Bana; Ramanjit Kaur; Yashbir Singh Shivay; Anil K. Choudhary; Teekam Singh; Samrath Lal Meena; Dunna Vijay; H. P. Vijayakumar; Vipin Kumar; Achchhelal Yadav (Agriculture, 2024)
Little mallow (Malva parviflora L.) is a notorious weed that causes substantial yield losses in winter crops. For effective weed management and seed testing, a deeper understanding of seed dormancy, germination behavior, and dormancy-breaking methods is necessary. Experiments were conducted to determine the effect of seed treatments, i.e., mechanical scarification, acid scarification, hot water treatment, and different germinating temperatures, i.e., 15 °C, 20 °C, or alternating 15–20 °C (16/8 h), on the seed dormancy in M.parviflora. A large proportion of M. parviflora seeds were physically dormant, with just 10.90% germination. Seed treatments had a significant influence on seed germination, seedling dry weight, vigor index, and water absorption (p ≤ 0.01). Among the various treatments, mechanical scarification enhanced germination by 32%, the vigor index by 487% and water uptake by 34%, and decreased percent hard seeds by 34%. Among the various germination temperatures, alternating 15–20 °C temperatures (16/8 h) gave the most significant result for germination and the lowest percent hard seeds. The findings of this study will serve as a valuable reference for seed testing and the development of suitable weed control strategies for M. parviflora.